2022
DOI: 10.3390/rs14133081
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Prediction of Reclaimed Coastal Airports with InSAR Observation: A Case Study of the Xiamen Xiang’an International Airport, China

Abstract: Many coastal cities reclaim land from the sea to meet the rapidly growing demand for land caused by population growth and economic development. Settlement in reclaimed land may delay construction and even damage infrastructures, so accurately predicting the settlement over reclaimed areas is important. However, the limited settlement observation and ambiguous final settlement estimation affect accurate settlement prediction in traditional methods. This study proposes a new strategy to solve these problems by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Xiong (2022) calculated the deformation of the tailings pond in Salt Lake County, Utah, based on the multi-temporal InSAR method to calculate the deformation of the reclaimed land area of Xiamen Xiang’an International Airport, using only Sentinel-1 data without the help of other SAR data and hydrological data. After comparing the fitted curves calculated by the hyperbolic model, Poisson model, and exponential model, it was found that the exponential curve model and the Asaoka method could better predict the final settlement and the consolidation time [ 34 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xiong (2022) calculated the deformation of the tailings pond in Salt Lake County, Utah, based on the multi-temporal InSAR method to calculate the deformation of the reclaimed land area of Xiamen Xiang’an International Airport, using only Sentinel-1 data without the help of other SAR data and hydrological data. After comparing the fitted curves calculated by the hyperbolic model, Poisson model, and exponential model, it was found that the exponential curve model and the Asaoka method could better predict the final settlement and the consolidation time [ 34 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang Zhengrong 7 used the glacier deformation field and gray correlation analysis obtained by InSAR technology and revealed the relationship between glacier deformation and various factors such as temperature, precipitation, and slope. Xiong Zhiqiang 8 used the statistical properties of curve fitting to select the best curve model from several candidate curve models to predict the subsidence time series. Shi Xianlin 9 used the regenerative settlement information combined with InSAR technology and Terzaghi theory and the corresponding geological parameters of the artificial airport to successfully deduce the predicted settlement curve of the offshore artificial island airport.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis and prediction of bad reclamation impacts must be held to prevent any further disadvantages that will also happen to society themselves (Li, 2014;Xiong et al, 2022). Thus, modeling and simulation can be chosen to be the most effective and efficient methods to achieve that goal.…”
Section: Introductionmentioning
confidence: 99%